مساهمة الشیخ محمد عبدالحکیم شرف القادری في تطوير العلوم العربیة فی باکستان: Al-Sheikh Muhammad Abdul Hakeem Sharaf Al-Qadri: Great Scholar of Uloom-e-Arabia in Pakistan - د. افتخار احمد خان; د.شهامد علی طاهر (JAR, 2023)
This article entitled “Al-Sheikh Muhammad Abdul Hakeem Sharaf Al-Qadri: Great Scholar of Uloom-e-Arabia in Pakistan” deals with the contribution of Al-Sheikh Muhammad Abdul Hakeem Sharaf Al-Qadri (1944 – 2007). He is one of the greatest scholars of Arabic and Islamic sciences in Pakistan. He engaged himself for the services of Arabic and Islamic literature and contributed a lot to heritance. He is one of those writers who laid down the methods for Islamic research. He wrote many books on various topics. Through his modern work like “Anwar-ul-Furqan” in the translation of the meanings of the Holy Quran & Al-Mardah commentary on the great book of logic “Al-Marqath”, The changed the currents in translation & commentary. Through deep study of his work it appears to us the style of Abdul Hakeem was known for its characteristics which may be summarized as follows: compact language, deep view, defence of realities, total control over language and comparison between various views. In short he appears to be the master of both the fields i.e. Arabic & Islamic literature.